Digital Media Research in Education: the Usefulness of the Instrumental Conflicts Theory - Pascal Marquet (Faculty of Engineering, Universitas Negeri Yogyakarta, 2017)
The purpose of this presentation is to define and to illustrate the concept of instrumental conflict, as a tool to a better understanding of the difficulties that learners encounter while using ICT (Information and Communication Technologies). An instrumental conflict takes its meaning within the framework of Rabardel’s theory of instruments, which in itself is a part of the more general theory of activity. The main idea is that VLE (Virtual Learning Environments) associate three different types of artefacts: didactical, pedagogical and technical. These artefacts must be correctly combined, so that learners can have access to knowledge, which is embedded in the device. We point out the usefulness of such a concept. We thus describe how scientific communities, which focus on didactics of Mathematics and computer science, and on ICT in education and training in particular, deal with difficulties of implementation and exploitation of ICT. It appears that some objects called either didactical objects or pedagogical objects represent a reality, which is similar and extremely wide at the same time. In fact, this ambiguity justifies the distinction between didactical artefacts, pedagogical artefacts and technical artefacts. We finally give some examples of obstacles that can be considered as instrumental conflicts as well as some possible developments offered by the concept of instrumental conflict.